Vibrational, Optical Band Gap, Urbach Energy, and Thermal Activation Analysis of TiO2/CaTiO3 Perovskite - Kormil Saputra; Dian Wijaya Kurniawidi; Aws M Aseer Nejres (CV. Abhinaya Indo Group, 2026)
TiO₂/CaTiO₃ is an oxide perovskite with considerable potential for photocatalytic, optical-sensing, and semiconductor-based functional-material applications. This study aimed to evaluate the vibrational characteristics, optical properties, band gap energy, Urbach energy, and kinetic and activation thermodynamic parameters of TiO₂/CaTiO₃.. The material was characterized using FTIR, UV–Vis spectroscopy, Kubelka–Munk analysis, Tauc plots, and Differential Thermal Analysis (DTA). The FTIR results revealed characteristic absorption bands in the low-wavenumber region associated with Ti–O, Ti–O–Ti, and Ca–O–Ti vibrations, indicating the formation of the TiO₂/CaTiO₃ perovskite framework. The UV–Vis spectrum showed dominant absorption in the ultraviolet region with an extension toward the visible region. Kubelka–Munk analysis yielded direct and indirect band gap energies of 2.896 and 2.897 eV, respectively, whereas the Tauc-plot method produced values of 2.894 and 2.896 eV. The Urbach energies obtained using the Kubelka–Munk approach ranged from 0.173 to 0.189 eV, while the Tauc-plot approach yielded 0.449–0.686 eV. These differences demonstrate the sensitivity of the estimation method to the baseline and fitting region and indicate the presence of tail states associated with optical disorder. DTA analysis showed a peak temperature of 623.31 K, with Ea = 7.853 kJ mol-1, ΔH* = 1.511 kJ mol-1, ΔG* = 233.89 kJ mol-1, ΔS* = −301.26 J mol-1 K-1, and ln A = −5.238. Overall, TiO2/CaTiO3 exhibited vibrational, optical, and thermal characteristics that support its potential as an oxide-perovskite functional material.